Optical coherence tomographic assessment of macular thickness and morphological patterns in diabetic macular edema: Prognosis after modified grid photocoagulation - Shrestha, A; Maharjan, N; Shrestha, A; Thapa, R; Poudyal, G (Nepalese Journal of Ophthalmology, 2012)
Introduction: The topographic mapping is useful for monitoring patients for the development of macular edema and following the resolution of edema after laser treatment. Objectives: To evaluate the usefulness of optical coherence tomography (OCT) for mapping of macula after laser therapy in clinically significant macular edema (CSME). Materials and methods: A prospective study was carried out enrolling 60 eyes of 35 patients with the diagnosis of CSME. OCT was performed at first visit and every successive follow up visit. The retinal thickness was measured automatically using OCT retinal mapping software. Statistics: Correlation between vision status and central macular thickness (CMT) was done using the Spearman’s correlation test. The analysis of variance (ANOVA) and independent t-test were used for comparison of groups. Results: The OCT revealed sponge like thickening pattern (ST) in 67.4 % followed by cystoid macular edema (CME) in 19.6 %. Best corrected visual acuity (BCVA) improved in 89.1 % after 6 months of treatment. There was high correlation between vision status and CMT (P =